The art of thinking clearly - Dobelli, Rolf, 1966-; Griffin, Nicky (London, Sceptre, 2014)
An exploration of human reasoning reveals how to recognize and avoid simple errors in our day-to-day thinking in order to transform the decision-making process
Why you should visit cemeteries : survivorship bias -- Does Harvard make you smarter? : swimmer's body illusion -- Why you see shapes in the clouds : clustering illusion -- If fifty million people say something foolish, it is still foolish : social proof -- Why you should forget the past : sunk cost fallacy -- Don't accept free drinks : reciprocity -- Beware the "special case" : confirmation bias (part 1) -- Murder your darlings : confirmation bias (part 2) -- Don't bow to authority : authority bias -- Leave your supermodel friends at home : contrast effect --
Translation of: Die Kunst des klaren Denkens
In the title the word "thinking" is printed upside down
Includes bibliographical references
Keywords: Reasoning (Psychology); Errors -- Psychological aspects; Decision making; Cognition